Mandarin e-learning system based on MOODLE for non-native learner / Norazzaleza Bertly - Bertly, Norazzaleza (2018)
Mandarin Language is one of the popular language taken in Universiti Teknologi MARA (UiTM), therefore the used of e-learning is one ways of deliver the course to learners. Mandarin languages have four different tones, which is the Hanyu Pinyin. Learning a new language take longer time to master, therefore the time to teach and learn Hanyu Pinyin is insufficient. The title of this study is Mandarin e-learning system based on MOODLE for non-native learner. The objective of this study is to identify the features of e-learning system based on MOODLE platform, to construct a Mandarin e-learning system for nonnative learners and to evaluate the ability to read Mandarin texts using the system. MOODLE platform is selected because it suitable to deliver the learning content by supporting multimedia elements. MOODLE platform consists of three module, which is administration module, user module and course module that is used to create Mandarin elearning system. The method in this study used between subject designs to test the system based on six respondents that divided into two groups, which test group and control group. This study compares the achievement of reading the Hanyu Pinyin for both groups whereby the test group adopts the Mandarin e-learning system and the control group adopts the traditional approach as the mode of learning. As the result, Mandarin e-learning system is based on Mandarin Module 1 in UiTM, the system is evaluated by undergraduate student, which are currently taking Mandarin module 1. Evaluation result shows that the respondent tempted to use longer sentences after using the system. They admitted have better understanding the meaning through translated Malay subtitles.